Detection of anti-toxoplasma gondii antibodies in wild free-living birds and mammals from the northwest region of são paulo state, brazil - Castiglioni, Lilian; Aires, Luiz Paulo Nogueira; Ferrari, Vinícius Matheus [UNESP]; Murata, Fernando Henrique Antunes; Soares, Herbert Sousa; Gennari, Solange Maria; Machado, Juliana Giantomassi; Fracischetti, Adriana Santiago; Sartori, Ricardo Quitério [UNESP]; de Mattos, Luiz Carlos; Brandão, Cinara Cássia; Pena, Hilda Fátima Jesus (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2021)
Toxoplasmosis is a protozoonosis caused by an obligate intracellular parasite named Toxoplasma gondii, which can infect humans and a large number of homeothermic animal species with worldwide distribution. The present study aimed to detect anti-T. gondii antibodies from serological samples of free-living wild animals from the northwest region of São Paulo state, Brazil. Thirty-two samples (eight from birds and 24 from mammals) were analyzed by the modified agglutination test (MAT) using 5 cut-off points for birds and 25 for mammals. Seropositivity was observed in 25% (2/8) of birds, including the species Rupornis magnirostris (roadside hawk) and Caracara plancus (southern caracara), and 29.2% (7/24) animals were seropositive among mammals, including one hoary fox (Lycalopex vetulus), two maned wolves (Chrysocyon brachyurus), one black howler monkey (Alouatta caraya), two crab-eating foxes (Cerdocyon thous) and one gray brocket deer (Mazama gouazoubira). The results obtained with the present study indicate the exposure to T. gondii of free-living wild animals from the northwest region of São Paulo state and, therefore, that they probably play a role in the transmission and maintenance of T. gondii in the environment they inhabit. Thus, identification of the infection in several animal species in the region indicates the environmental contamination of the area. Studies of this nature may help to understand the importance of the prevention and control of this disease in Brazil.
Detecção de anticorpos anti-toxoplasma gondii em aves e mamíferos silvestres de vida livre da região noroeste do estado de são paulo, brasil
Keywords: MAT; Occurrence; Serology; Toxoplasmosis; Wildlife; Zoonosis